A Large Eddy Model Study on the Effect of Overshooting Convection on Lower Stratospheric Water Vapor. Issue 18 (17th September 2018) - Sang, Wenjun; Huang, Qian; Tian, Wenshou; Wright, Jonathon S.; Zhang, Jiankai; Tian, Hongying; Luo, Jiali; Hu, Dingzhu; Han, Yuanyuan
Abstract: Using a cloud‐resolving large eddy model (LEM), we investigate how overshooting convection affects the water vapor content in the lower stratosphere. We design and conduct a series of sensitivity experiments to diagnose the effects of dynamical and thermodynamical background conditions on the transport of water vapor into the lower stratosphere associated with overshooting convection. The three‐dimensional LEM simulations capture the bulk properties of the target case and track microphysical processes using a three‐phase microphysical parameterization. The model results indicate that the net effect of overshooting convection on lower stratospheric water content is moistening, primarily due to gravity wave breaking and ice sublimation. The contributions of small‐scale turbulent mixing to water vapor transport from the overshooting turret into the stratosphere are relatively weak. Sensitivity experiments show that convective intensity (as measured by updraft velocity) is directly related to the effect of overshooting convection on lower stratospheric humidity. This impact is quantified for the idealized target case. Changes in vertical wind shear near the tropopause have no significant impact on the extent of overshooting but have important impacts on cross‐tropopause water vapor exchange via their modulation of gravity wave breaking. Larger vertical wind shear in the tropopause layer inhibits the transport of water vapor and ice into the lower stratosphere by overshooting convection. Key Points: Idealized simulations of overshooting tropical convection indicate net moistening of the lower stratosphere Stratospheric moistening results from ice sublimation and gravity wave breaking near the tropopause Effects of near‐tropopause vertical wind shear are mainly through modulation of gravity wave breaking rather than turbulent mixing